2006
DOI: 10.11646/zootaxa.1202.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Carraroenia ruthae gen. et sp. nov. (Copepoda, Harpacticoida, Laophontidae) from maerl substrates of the Irish west coast

Abstract: Carraroenia ruthae gen. et sp. nov. is described from maerl beds at An Dóilín, Carraroe, County Galway, Ireland. This genus is considered to be closely related to the genus group comprising Psammplatypus, Coullia, Phycolaophonte, Hemilaophonte and Robustunguis, which had been linked based on the reduced P2 endopod and the primitive setation of the male P5 baseoendopod. Carraroenia is regarded as the most primitive genus of this lineage, as evidenced by the 3segmented male P3 endopod, the lack of reduction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The significance of patterns of swimming leg sexual dimorphism in unravelling relationships among certain laophontid lineages has been demonstrated repeatedly in a number of studies (e.g., Lee and Huys 1999; Gómez and Boyko 2006; McCormack 2006; Huys and Lee 2009). However, except for the apophysis on the male P3 endopod (Figure 6C) no other sexual dimorphism is expressed on legs 2–4 of P. aspidosoma .…”
Section: Discussionmentioning
confidence: 90%
“…The significance of patterns of swimming leg sexual dimorphism in unravelling relationships among certain laophontid lineages has been demonstrated repeatedly in a number of studies (e.g., Lee and Huys 1999; Gómez and Boyko 2006; McCormack 2006; Huys and Lee 2009). However, except for the apophysis on the male P3 endopod (Figure 6C) no other sexual dimorphism is expressed on legs 2–4 of P. aspidosoma .…”
Section: Discussionmentioning
confidence: 90%
“…Lee and Huys (1999) discussed the relationship between Psammoplatypus and related genera based on the reduced P2 endopod, the swimming leg sexual dimorphism and the ovate shape of female P5 exopod. Additionally, McCormack (2006) observed that the species Carraroenia ruthae McCormack, 2006 shares some characters with this lineage. Huys (2009) consequently suggested that Phycolaophonte and Eolaophonte should be subsumed into the synonymy of Coullia and provided a key to genera which have reduced P2 including the five genera Carraroenia , Coullia , Hemilaophonte , Psammoplatypus and Robustunguis .…”
Section: Discussionmentioning
confidence: 98%
“…The new genus, Jejulaophonte is placed in the subfamily Laophontinae based on character sets including the sub-chirocer male antennule, the typically uniramous mandible, the syncoxa of maxilliped armed with maximum only two setae, the P1 enp-1 without inner seta, the reduced P2 enp-2 without outer spine, and the proximal outer setae of female P5 exopod with a distinctly separated insertion site. Jejulaophonte is closely related to five genera ( Carraroenia McCormack, 2006, Coullia Hamond, 1973, Hemilaophonte Jakubisiak 1933, Psammoplatypus Lee & Huys, 1999, and Robustunguis Fiers, 1992), the CCHPR-lineage, based on the reduced P2 endopod (Laophontidae typically has P2 larger than P3), the ovate shape of female P5 exopod, and the sexual dimorphism in the P3 endopod (Gomez and Boyko 2006, Huys 2009, McCormack 2006). Fiers (1992a, b) claimed that the main reason for some species of the genera Robustunguis and Hemilaophonte having reduced appendages is to adapt to their host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies on meiofauna suggest that maerl beds support a high biodiversity, including a high diversity of bivalves compared with other substrata (Jackson et al 2004) and a new genus of Copepoda from the Irish west coast (McCormack 2006). Furthermore, a high species richness of foraminifera on Scottish coasts has led maerl beds to become an important near-shore habitat in regional studies of benthic foraminiferal distribution/ecology (Austin and Cage 2010).…”
Section: Introductionmentioning
confidence: 99%